Polarities of Compulsory Education from the Perspective of Parents and Kindergarten Teachers - Majerčíková, Jana; Navarátilová, Hana (European Journal of Social Science Education and Research, 2021)
This empirical study deals with the issue of compulsory education in kindergartens, which was implemented in the Czech Republic in 2017. Children aged 5 must attend kindergarten or opt for individual home-schooling. The intention of this Czech educational policy step was to raise the preparedness and eligibility of children for compulsory primary school education and to eliminate or compensate for potential handicaps when detected. The aim of the research was to document the reflections of parents and kindergarten teachers on the realization of the compulsory pre-school education, specifically the concerns and other reactions of the adults and the children themselves. The data collection was performed by two means: a questionnaire filled in by 305 parents within which predominantly open questions were analyzed, and the method of thematic writing by kindergarten teachers. In the second case twenty-nine texts averaging 2500 characters were obtained. To process the data we used the content analysis method based on open coding. Several significant findings were disclosed characterizing compulsory pre-school education, notably regarding ambivalence. The parents’ attitudes are based on preferences and necessities of pre-school education (as opposed to individual home-schooling) for their children’s further educational career, however, the strict legal obligation to ensure children’s kindergarten attendance was disputed. The teachers welcome the expected improvement of the children’s preparedness; at the same time, they perceive a borderline shift regarding the follow-up childhood stage traditionally connected with entering primary school. The teachers also identify the changing attitudes of children in transition from an institution where they “go to play” while their parents work, to that of a learning place with a status similar to that of primary school.
Keywords: compulsory pre-school education, kindergarten teacher, parent, legislative change